Greenhouse Gas Emissions Dynamics in Restored Fens After In-Situ Oil Sands Well Pad Disturbances of Canadian Boreal Peatlands - Lemmer, Meike; Rochefort, Line; Strack, Maria (Frontiers in Earth Science, 2020)
In-situ oil extraction activities impact the vast mosaic of boreal wetlands and uplands. Peatland restoration in these regions aims at reestablishing crucial peatland functions, such as peat accumulation and carbon (C) sequestration. In order to assess the success of fen restoration, we evaluated the biogeochemical conditions, the seasonal carbon balances via carbon dioxide (CO2) fluxes and methane (CH4) emissions, and addressed the global warming potential following different restoration techniques at two restored in-situ oil sands well pads, during two consecutive growing seasons. Restoration work involved: 1) the partial or complete removal of introduced well pad construction materials, and spontaneous revegetation, or 2) the partial removal of foreign clay, in addition to reintroduction of typical fen plant species such as Larix laricina, Salix lutea and Carex aquatilis. Comparisons were done with regional reference ecosystems (REF) consisting of three peatlands: a wooded bog, a wooded rich fen and a wooded extreme-rich fen. While the average electric conductivity of restored sectors (946 μS cm−1) was higher compared to REF (360 μS cm−1), the pH was quite similar (pH 5.8 REF, pH 6 restored). Dissolved organic carbon concentration was lower in all restored sectors (5–11 mg L-1 restored sectors, 15–35 mg L-1 REF), presumably due to the still incomplete recovery of vegetation and lower organic matter content associated with remnant well pad material. Re-establishment of shrub and brown moss species improved significantly the C uptake. However, the active introduction of plant species was no crucial restoration step, in order to return species beneficial for C uptake. Restoration treatments that were leveled closest to the surrounding REF showed the most similar seasonal C balance to REF. In shallow open water areas resulting from the complete removal of all construction materials, we measured the highest methane emissions making these flooded sites net C sources to the atmosphere with elevated global warming potential. The partial removal of the well pad’s mineral soil to near the water table level and the surface elevation of the surrounding ecosystem seems to be the most effective site management method to sequester carbon efficiently. However, further research is needed to evaluate the suitability of this restoration method for the recovery of biodiversity and possible impacts of residual foreign materials on fen ecosystems.